Ginsenoside Rg1 ameliorates blood-brain barrier disruption and traumatic brain injury via attenuating macrophages derived exosomes miR-21 release - Kefeng Zhai; Hong Duan; Wei Wang; Siyu Zhao; Ghulam Jilany Khan; Mengting Wang; Yuhan Zhang; Kiran Thakur; Xuemei Fang; Chao Wu; Jianbo Xiao; Zhaojun Wei (Elsevier, 2021)
During the traumatic brain injury (TBI), improved expression of circulatory miR-21 serves as a diagnostic feature. Low levels of exosome-miR-21 in the brain can effectively improve neuroinflammation and blood-brain barrier (BBB) permeability, reduce nerve apoptosis, restore neural function and ameliorate TBI. We evaluated the role of macrophage derived exosomes-miR-21 (M-Exos-miR-21) in disrupting BBB, deteriorating TBI, and Rg1 interventions. IL-1β-induced macrophages (IIM)-Exos-miR-21 can activate NF-κB signaling pathway and induce the expressions of MMP-1, -3 and -9 and downregulate the levels of tight junction proteins (TJPs) deteriorating the BBB. Rg1 reduced miR-21-5p content in IIM-Exos (RIIM-Exos). The interaction of NMIIA-HSP90 controlled the release of Exos-miR-21, this interaction was restricted by Rg1. Rg1 could inhibit the Exos-miR-21 release in peripheral blood flow to brain, enhancing TIMP3 protein expression, MMPs proteolysis, and restricting TJPs degradation thus protected the BBB integrity. Conclusively, Rg1 can improve the cerebrovascular endothelial injury and hold the therapeutic potential against TBI disease.